2010
DOI: 10.3109/14992021003685817
|View full text |Cite
|
Sign up to set email alerts
|

Exploring hearing aid use in older women through narratives

Abstract: This study explored experiences surrounding hearing aid use and non-use in older women with hearing loss. A narrative approach was used to gain an in-depth understanding of the meaning and contextual issues that impact upon the adaptation process of older adults and their transitions in using hearing devices. Four women over the age of sixty who were identified as being consistent hearing aid users took part in three face-to-face interviews. Wengraf's (2001) biographic-narrative-interview guiding framework was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 27 publications
6
68
0
Order By: Relevance
“…Therefore this study extends the previous findings as it highlights how self-assessment is central to adults with hearing impairment when sharing both their experiences but also their expectations. Lockey et al (2010) identified the central role of participation in determining hearing-aid use in four older Canadian women and the present study depicts similar concepts in a sample of 34 men and women of various ages and countries. Finally, the importance of a client-centered approach reported in this study, for example with participants valuing clinicians who have a genuine interest in them, echoes previous qualitative research (Laplante-Lévesque et al, 2010a).…”
Section: Discussionsupporting
confidence: 73%
“…Therefore this study extends the previous findings as it highlights how self-assessment is central to adults with hearing impairment when sharing both their experiences but also their expectations. Lockey et al (2010) identified the central role of participation in determining hearing-aid use in four older Canadian women and the present study depicts similar concepts in a sample of 34 men and women of various ages and countries. Finally, the importance of a client-centered approach reported in this study, for example with participants valuing clinicians who have a genuine interest in them, echoes previous qualitative research (Laplante-Lévesque et al, 2010a).…”
Section: Discussionsupporting
confidence: 73%
“…A later step in the analysis can include linking the experiences of a specific phenomenon to the wider social, cultural, and political context. Interpretative phenomenology has been widely used in health research and has also been applied to research in audiology (e.g., Hétu et al, 1988;Lockey et al, 2010). Lockey and colleagues (2010) analysed biographic-narrative-interviews with older women with hearing impairment by using a interpretative phenomenological approach.…”
Section: Four Theoretical/methodological Approachesmentioning
confidence: 99%
“…In this iterative interview process several in-depth structured interviews are conducted with the same participant. Participants are typically invited to review and comment on the construction of storylines and thematic analysis that the researcher carries out (e.g., Lockey et al, 2010). …”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory overload is a common concern about hearing aids. Sensory overload is correlated with the length of time the older adult has lived with uncorrected hearing loss (Lockey, Jennings, & Shaw, 2010). People often delay acquiring hearing aids because the loss occurs gradually, and people tend to compensate by ignoring and denying the loss (Lane, 2012).…”
Section: To Hear or Not To Hearmentioning
confidence: 99%